Do hotel financial factors influence satisfaction?. (September 2021) - Alexakis, Christos; Dowling, Michael; Pappas, Vasileios; Ramachandiran, Manimozhi; Skalvos, Favianos
Highlights: Financial measures are related to hotel guest satisfaction. Investment in guest amenities is particularly important for satisfaction. Long-term is preferred to short-term investment.